The effects of thymic stromal lymphopoietin and IL‐3 on human eosinophil–basophil lineage commitment: Relevance to atopic sensitization. Issue 1 (9th May 2014) - Hui, Claudia C. K.; Rusta‐Sallehy, Sina; Asher, Ilan; Heroux, Delia; Denburg, Judah A.
Abstract An important immunopathological hallmark of allergic disease is tissue eosinophilic and basophilic inflammation, a phenomenon which originates from hemopoietic progenitors (HP). The fate of HP is determined by local inflammatory cytokines that permit "in situ hemopoiesis, " which leads to the accumulation of eosinophils and basophils (Eo/B). Given that recent evidence supports a critical immunomodulatory role for thymic stromal lymphopoietin (TSLP) in allergic inflammation, as well as TSLP effects on CD34+ progenitor cytokine and chemokine secretion, we investigated the role of TSLP in mediating eosinophilo‐ and basophilopoiesis, the mechanisms involved, and the association of these processes with atopic sensitisation. In the studies presented herein, we demonstrate a direct role for TSLP in Eo/B differentiation from human peripheral blood CD34+ cells. In the presence of IL‐3, TSLP significantly promoted the formation of Eo/B colony forming units (CFU) (including both eosinophils and basophils) from human HP (HHP), which was dependent on TSLP–TSLPR interactions. IL‐3/TSLP‐stimulated HHP actively secreted an array of cytokines/chemokines, key among which was TNFα, which, together with IL‐3, enhanced surface expression of TSLPR. Moreover, pre‐stimulation of HHP with IL‐3/TNFα further promoted TSLP‐dependent Eo/B CFU formation. HHP isolated from atopic individuals were functionally and phenotypically more responsive to TSLP than those from nonatopic individuals. This is the first study to demonstrate enhanced TSLP‐mediated hemopoiesis ex vivo in relation to clinical atopic status. The capacity of HHP to participate in TSLP‐driven allergic inflammation points to the potential importance of "in situ hemopoiesis" in allergic inflammation initiated at the epithelial surface.